Position statement of the Polish Society of Gastroenterology on the use of andexanet alfa in patients with gastrointestinal bleeding taking factor Xa inhibitors - Adrych, Krystian; Daniluk, Jarosław; Nowakowska-Duława, Ewa; Białek, Andrzej; Rydzewska, Grażyna M. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2025)
In Poland, there has been a steady increase in the number of patients receiving factor Xa (FXa) inhibitors as part of anticoagulant therapy. Despite their high therapeutic efficacy and the lack of a need for dose monitoring, these agents are responsible for serious bleeding (including gastrointestinal bleeding) in approximately 1–4% of patients. Until recently, the management of gastrointestinal bleeding in patients receiving FXa inhibitors relied on non‑specific measures, such as fluid resuscitation, blood product transfusions, and the administration of prothrombin complex concentrate or recombinant factor VIIa. Andexanet alfa is a recombinant, inactive analogue of human FXa which specifically and effectively reverses the activity of FXa inhibitors, namely rivaroxaban and apixaban. Previous research has demonstrated the efficacy of andexanet alfa in achieving haemostasis and reducing mortality. This agent should be used in patients receiving an FXa inhibitor who present with life‑threatening or uncontrolled gastrointestinal bleeding, accompanied by hypovolaemia and haemodynamic instability, and who fail to respond to initial fluid resuscitation or experience persistent bleeding despite endoscopic intervention. This article presents the position of the experts of the Polish Society of Gastroenterology regarding the management of patients with gastrointestinal bleeding taking FXa inhibitors and the indications for the use of andexanet alfa.